2000
DOI: 10.1021/jp9938112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Low-Energy (0.5−30 eV) Electron-Induced Pyrimidine Ring Fragmentation within Thymine- and Halogen-Substituted Single Strands of DNA

Abstract: Low-energy (0.5-30 eV) electron irradiation of the thymine-and halogen-substituted nonamers Au/Cy* 6 T 3 and Au/Cy* 6 (FU,BrU,IU) 3 , chemisorbed onto a gold surface, leads to the desorption of neutral CN and OCN from fragmentation of the DNA base ring. No neutral halogen-containing species are detected. The cross sections at 15 eV for CN and OCN desorbing from the substituted oligomers bromouracil, fluorouracil, iodoracil, and thymine are measured to be 7.5-, 4.5-, (2.5-3.0)-, and (3.0-3.5) × 10 -17 cm 2 , re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 39 publications
5
41
0
1
Order By: Relevance
“…The studies [157][158][159][160][161][162][163][164][165][166][167] confirmed the prediction of Zimbrick and coworkers [168] that the radiosensitizing properties of these compounds arose from DEA of solvated electrons, and further showed that DEA of higher energy (0-7eV) electrons was also involved in radiosensitization. Platinum bromide, aromatic compounds containing nitro group and other halogenated thymidine derivatives were found to play similar roles [58, 70, 71, 163-165, 169, 170].…”
Section: Transient Anions In Halogen Compoundssupporting
confidence: 75%
See 1 more Smart Citation
“…The studies [157][158][159][160][161][162][163][164][165][166][167] confirmed the prediction of Zimbrick and coworkers [168] that the radiosensitizing properties of these compounds arose from DEA of solvated electrons, and further showed that DEA of higher energy (0-7eV) electrons was also involved in radiosensitization. Platinum bromide, aromatic compounds containing nitro group and other halogenated thymidine derivatives were found to play similar roles [58, 70, 71, 163-165, 169, 170].…”
Section: Transient Anions In Halogen Compoundssupporting
confidence: 75%
“…Following early investigations with solvated electrons [168], a relatively large number of experiments have been performed both in the gas (see Section 4.4) and condensed phases [160,161,165] to study electron scattering from--and attachment to--halogenated pyrimidines. Several experiments were performed using SAMs of BrdU-containing oligonucleotides [157,158,171]. These included the detection of the electron-stimulated desorption of ion and neutral species and HPLC analysis of damaged films, as well as electronic and vibrational electronenergy loss spectra for gaseous bromouracil [159].…”
Section: Transient Anions In Halogen Compoundsmentioning
confidence: 99%
“…8,11,12 Here we show the most likely products resulting from breaking of the N-H or C-H bonds. Figure 4 exhibits the spin density on the departing H as the N-H or C-H distance is stretched.…”
Section: Charge and Spin Distribution As The H Atom Recedesmentioning
confidence: 80%
“…It was also found that LEEs can induce ring fragmentation of DNA bases, such as thymine and halouracils. 11,12 The reason uracil dissociates so easily on LEE attachment has been attributed to the high electron affinities (EA) of the U-yl radicals, 8 which are formed by detaching one of the four hydrogen atoms at the N 1 , N 3 , C 5 , or C 6 positions. The energy released by the binding of an electron to the U-yl radical reduces the overall energy needed to fragment an N-H or C-H bond.…”
Section: Introductionmentioning
confidence: 99%
“…Hence their effective ranges is short; so that their interactions with bio-molecules can be studied using electron impact techniques on thin sample films, and for such work, self-assembled monolayers (SAMs) offer certain advantages, in particular their (relatively) easy preparation, uniformity, and high density and supposed high order. Previous researchers from our laboratory have adsorbed thiolated DNA onto gold to determine electron attenuation lengths and effective damage cross sections in DNA SAMs [26] and to measure the electron stimulated desorption (ESD) of neutral [27,28] and of anionic [22] species from DNA. In this latter work, single-and double-stranded (ss and ds, respectively) DNA oligonucleotides of 40 base pairs, were attached to gold by either a single terminal thiol (1S) or by five thiols (5S) positioned with a spacing of ~8 base pairs along the sugar-phosphate backbone.…”
Section: Introductionmentioning
confidence: 99%